2013
DOI: 10.1002/hep.26094
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a myeloid cell subset (CD11b/Gr1mid) via CCL2/CCR2 promotes the development of colorectal cancer liver metastasis*

Abstract: Liver metastasis from colorectal cancer is a leading cause of cancer mortality. Myeloid cells play pivotal roles in the metastatic process, but their prometastatic functions in liver metastasis remain incompletely understood. To investigate their role, we simulated liver metastasis in C57BL/6 mice through intrasplenic inoculation of MC38 colon carcinoma cells. Among the heterogeneous myeloid infiltrate, we identified a distinct population of CD11b/Gr1 mid cells different from other myeloid populations previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
176
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(187 citation statements)
references
References 30 publications
11
176
0
Order By: Relevance
“…Kowanetz and colleagues showed that suggesting that direct interaction of the tumor cell-derived chemokine with monocytes is necessary for efficient tumor cell extravasation (67). In contrast, metastasis of B16-BL6 melanoma cells was independent of CCR2 expression, suggesting that some tumor cells use other means for tumor cell extravasation which remain to be determined (67,68).…”
Section: Ccl2-ccr2 Anti-metastatic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Kowanetz and colleagues showed that suggesting that direct interaction of the tumor cell-derived chemokine with monocytes is necessary for efficient tumor cell extravasation (67). In contrast, metastasis of B16-BL6 melanoma cells was independent of CCR2 expression, suggesting that some tumor cells use other means for tumor cell extravasation which remain to be determined (67,68).…”
Section: Ccl2-ccr2 Anti-metastatic Activitymentioning
confidence: 99%
“…CCL5-expressing tumor cells showed a significant reduction in lung metastasis in S100A4 -/-mice, while liver metastasis was not affected, indicating that at least metastases to the lungs are highly dependent on the interplay between CCL5 and S100A4. Despite these open questions, inhibition of CCL2 or CCR2 was reported to be beneficial in inhibiting metastasis of various cancer types such as breast, bladder, colorectal or prostate cancer in experimental models (66)(67)(68). Based on this preclinical evidence, two clinical trials have been started, evaluating safety and efficacy of blocking both CCL2 and CCR2 in metastatic patients (http://www.clinicaltrials.gov: NCT00992186, NCT01015560).…”
Section: Chemokines and The Metastatic Nichementioning
confidence: 99%
See 1 more Smart Citation
“…One major bottleneck of metastatic inefficiency is dictated by the unique tissue microenvironments at secondary sites, called metastatic niches 18 , highlighting the importance of understanding site-specific metastasis. The metastatic niche is unique to the site of recurrence, and is, in part, characterized by deposition of distinct extracellular matrix proteins 19,20 , infiltration of various immune cell populations [21][22][23] , and altered tissue homeostasis including dysregulated production of numerous cytokines, chemokines, and growth factors 15,18,24,25 . Thus, an understanding of the tissue specific metastatic niche precedes an understanding of how to target metastatic disease.…”
Section: Introduction Breast Cancer Metastasis To the Livermentioning
confidence: 99%
“…In particular, initiation of metastasis is dependent on the recruitment of leukocytes that is mediated by chemokines (24,25). Tumorderived CCL2 expression drives the recruitment of inflammatory monocytes that facilitates tumor cell extravasation and thereby metastasis (26)(27)(28)(29). Yet, the mechanism of leukocyte adhesion and recruitment to metastatic tumors remains to be identified.…”
Section: Introductionmentioning
confidence: 99%